If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 6) = (5x + 18) Reorder the terms: (6 + 7x) = (5x + 18) Remove parenthesis around (6 + 7x) 6 + 7x = (5x + 18) Reorder the terms: 6 + 7x = (18 + 5x) Remove parenthesis around (18 + 5x) 6 + 7x = 18 + 5x Solving 6 + 7x = 18 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + 7x + -5x = 18 + 5x + -5x Combine like terms: 7x + -5x = 2x 6 + 2x = 18 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + 2x = 18 + 0 6 + 2x = 18 Add '-6' to each side of the equation. 6 + -6 + 2x = 18 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 18 + -6 2x = 18 + -6 Combine like terms: 18 + -6 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 9-3x-(-8y)+9x-y=0 | | 2.2(0.41+20.6)= | | 6x+2=3x+16 | | 61-6q=-11 | | 8x-9=47 | | 6x+2=9x+10 | | 5.4=-6.1+t | | 3(n-18)=2n+1 | | 10(x-1)=4x+26 | | 180=(3x+8) | | -4.4j-2=-5.5j-4.2 | | 4r+2+5r-12=125 | | 3a+4=18+a | | 1.9m-6.2=-14.6+4.7m | | 4(0)-3y=0 | | 6x-12=8x-16 | | =x+6y | | (g+4)-3a=1+g | | 6x+11=2x+5 | | -x+5=4x+71 | | 3(-2-5)+11= | | 3x+6=3x+22 | | 56-5x=13x+24 | | p-5(2-3)+1= | | .75(4x+8)=-12 | | 4x-3(0)=0 | | 5(3-2k)=8(3k-4)-4(1+7k) | | 4x+-2=3x+4 | | 3(2-X)+8=2(X-4)+6 | | y=3x^4-12x^3-24x^2-7 | | 2(x+4)=2(x-4)+4x | | .40x-9=7-.60x |